2018
DOI: 10.1136/bmjopen-2018-024144
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between right-to-left shunt and migraine in patients with epilepsy: a single-centre, cross-sectional study in China

Abstract: ObjectivesTo investigate the relationship between right-to-left shunt and migraine to account for the unexplained high prevalence of migraine in patients with epilepsy.DesignThis is a cross-sectional study. The diagnosis and interview process of patients with migraine was based on the International Classification of Headache Disorders-3 beta in patients with epilepsy. Participants underwent transthoracic echocardiography (TTE) with contrast medium to identify right-to-left shunt. The highest number of microbub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Consistently, several clinical reports have described improved symptoms of OSA and migraine, artery stiffness and vasodilation, nocturnal oxygenation, and overall quality of life after closure of RLS 50,51 . Interestingly, it has also been reported that the frequency of seizures in three PWEs with migraine decreased significantly after PFO closure 11 . Based on our analyses, RLS could be a prognostic or predictive biomarker of DRE and the detection of RLS could influence the decision‐making for PWEs with DRE.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consistently, several clinical reports have described improved symptoms of OSA and migraine, artery stiffness and vasodilation, nocturnal oxygenation, and overall quality of life after closure of RLS 50,51 . Interestingly, it has also been reported that the frequency of seizures in three PWEs with migraine decreased significantly after PFO closure 11 . Based on our analyses, RLS could be a prognostic or predictive biomarker of DRE and the detection of RLS could influence the decision‐making for PWEs with DRE.…”
Section: Discussionsupporting
confidence: 88%
“…Nowadays, it has been found that the high prevalence of RLS was correlated with the commodity of migraine in PWEs, which could be an underlying cause of migraine in PWEs 11 . Epilepsy is often comorbid with migraine, and they share similar symptom profiles, treatment options, and common pathogenic mechanisms, such as hypoxia, CSD, and microthrombi 12,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies included in this systematic review were published between 2004 and 2019 and the sample size ranging between 86 in Turkey and 1109 in China. Of 17 studies included the final meta-analysis, one from the USA [34], one from India [35], three from Iran [36][37][38], one from Japan [26], one from Taiwan [35], one from Italy [36], three from China [25,39,40], one from Turkey [41], one from Lithuania [42], one from Montenegro [43], one from Bangladesh [44] and two from Egypt [45,46]. Regarding types of headaches assessed among patients with epilepsy, nine studies assessed tension-type headache, fifteen studies assessed migraine with aura, three studies assessed migraine without aura, and seven studies assessed both Ictal headache (IH) and Postictal headache (PIH).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Epilepsy–migraine comorbidities are classified into epileptic migraine, pre-seizure migraine, post-seizure migraine, and inter-epileptic migraine. Among them, migraine after a seizure is the most common [ 7 , 8 ]. Compared with ordinary patients with epilepsy, the epilepsy symptoms of patients with epilepsy–migraine comorbidity are more difficult to alleviate, and the quality of life will be further reduced [ 9 ].…”
Section: Introductionmentioning
confidence: 99%